Low Occurrence of Patulin-Producing Strains of Penicillium in Grapes and Patulin Degradation During Winemaking in Chile - Yanez-Catalan, L (2011)
Penicillium expansum has emerged as the cause of storage decay of table grapes (Vitis vinifera) and has been frequently isolated from apparently healthy clusters of grapes in Chile. The objectives of this study were to identify patulin-producing strains of Penicillium associated with winegrapes and wineries in Chile and to determine the potential presence of patulin in wines made with grapes infected with P. expansum. In this study, P. brevicompactum, P. expansum, and P. glabrum were identified on apparently healthy grape clusters and in the air of vineyards and wineries. Of 132 Penicillium isolates, 4 P. brevicompactum and 11 P. expansum strains were patulin-producing, determined by HPLC-UV/DAD. Patulin was also detected in Cabernet Sauvignon musts produced with grapes contaminated with a patulin-producing strain of P. expansum. However, patulin concentrations decreased during fermentation by 67.3 to 83.3%. Overall, the frequency of P. expansum isolation from grapes was relatively low; thus, considering the rapid degradation of patulin produced during fermentation, the risk of patulin contamination of bottled wine appears to be low. © 2011 by the American Society for Enology and Viticulture.